Three-dimensional nanoporous metal and halogen ion-assisted electrochemical nanowelding preparation method and application thereof

CN115555748BActive Publication Date: 2026-11-03HUNAN UNIV
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202210981773.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-08-16
Publication Date
2026-11-03
Estimated Expiration
2042-08-16

AI Technical Summary

Technical Problem

现有方法在制备纳米多孔金时存在高能耗、资源浪费、腐蚀性介质使用及纯度影响等问题,且纳米多孔金的可调性和转移性不足。

Method used

A halide ion-assisted cyclic voltammetry electrochemical nanowelding method was adopted to achieve efficient welding of metal nanoparticles by electrochemically treating multilayer metal nanoparticle films in a halide ion-containing electrolyte, combined with interface self-assembly and plasma treatment, thus preparing three-dimensional nanoporous metals.

Benefits of technology

A highly efficient, low-temperature, and controllable nano-welding process was achieved, producing high-purity three-dimensional nanoporous metals. This solved the problems of over-welding and structural collapse, improving welding efficiency and material properties, and making it suitable for optical, electrical, electrochemical, and sensor devices.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115555748B_ABST
    Figure CN115555748B_ABST
Patent Text Reader

Abstract

The application belongs to the field of nano-porous material manufacturing, and specifically discloses a high-efficiency preparation method of halogen ion assisted electrochemical nano-welding of three-dimensional nano-porous metal, which comprises the following steps: performing cyclic voltammetry electrochemical nano-welding on three-dimensional precursors to be welded in an electrolyte containing halogen ions to obtain three-dimensional nano-porous metal; the three-dimensional precursors comprise metal particles stacked in a three-dimensional structure, and there are nano-gaps to be welded between the metal particles. The halogen ions and the cyclic voltammetry electrochemical nano-welding process are combined to achieve synergy, which is conducive to improving the welding effect and greatly improving the welding efficiency.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the technical field of nanoporous material fabrication, specifically to the field of nanowelding preparation of porous three-dimensional metals. Background Technology

[0002] Three-dimensional porous metals, such as three-dimensional nanoporous gold, have attracted much attention from researchers due to their unique properties such as large specific surface area, high electrical conductivity, plasmon resonance characteristics, electrochemical activity and biocompatibility. Furthermore, nanoporous gold has been applied in many fields such as energy storage, surface-enhanced Raman scattering, catalysis, and biochemical sensing.

[0003] Existing methods for preparing nanoporous gold mainly include dealloying, template-based methods, and electrochemical anodizing. Among these, dealloying and template-based methods are more commonly used, but these two methods suffer from problems such as high energy consumption, resource waste, the use of corrosive media, and residual sacrificial components (affecting the purity of the obtained nanoporous gold). Therefore, dealloying and template-based methods are not particularly ideal for preparing nanoporous gold. While the currently reported electrochemical anodizing method can rapidly prepare nanoporous gold, it still suffers from problems such as wasted gold source dissolution, difficulty in easily transferring the prepared nanoporous gold to different substrates, and the size of the obtainable nanoporous gold being limited by the size of the original gold electrode.

[0004] Due to the continuous development of nanomaterial synthesis technology, various special structures of gold nanomaterials can be easily prepared. This provides favorable support for the preparation of high-purity nanoporous gold using gold nanomaterials as basic building blocks. Although researchers have prepared nanoporous gold through methods such as pH-induced linear aggregation of Au nanoparticles to obtain nanoporous gold superstructures (e.g., sponges), halide ion-induced three-dimensional aggregation of Au nanoparticles, hydrochloric acid and thermal activation-light induced interfacial two-dimensional assembly of Au nanoparticles, and mercapto polyethylene glycol and hydrothermal treatment-induced three-dimensional self-assembly of Au nanoparticles, these methods have relatively poor versatility to some extent. This is because they require strict control of the operating conditions during the preparation process, and the tunability of the obtained nanoporous structures is not strong. Summary of the Invention

[0005] To address the problems of over-welding, etching, and low efficiency in the preparation technology of three-dimensional porous metal nano-welding, the primary objective of this invention is to provide a method for preparing three-dimensional nanoporous metals by halide ion-assisted high-efficiency electrochemical nano-welding. This aims to provide a novel approach to porous metal nano-welding and improve the preparation effect and efficiency.

[0006] The second objective of this invention is to provide a three-dimensional nanoporous metal prepared by the halide ion-assisted high-efficiency electrochemical nanowelding method.

[0007] The third objective of this invention is to provide the application of the three-dimensional nanoporous metal prepared by the halide ion-assisted high-efficiency electrochemical nanowelding method in the preparation of at least one device in optics, electronics, electrochemistry, and sensing.

[0008] The nano-welding process of three-dimensional porous metals enhanced by direct current is prone to problems such as local or overall over-welding and structural collapse. To address this issue, the present invention provides the following improvement:

[0009] A method for preparing three-dimensional nanoporous metals by halide ion-assisted electrochemical nanowelding involves performing cyclic voltammetry electrochemical nanowelding on the three-dimensional precursors to be welded in an electrolyte containing halide ions to obtain three-dimensional nanoporous metals.

[0010] The three-dimensional precursor is composed of stacked metal particles with nano-gap gaps between them to be welded.

[0011] This invention has found that electrochemical nanowelding using cyclic voltammetry, combined with the strengthening effect of halide ions, can achieve synergy and improve the efficiency and effectiveness of nanowelding.

[0012] In this invention, the three-dimensional precursor is a multilayer metal composite film (multilayer metal composite layer) formed by stacking two or more single-layer metal layers in sequence.

[0013] In this invention, the multilayer metal composite film can be prepared using existing methods. For example, the multilayer metal composite film can be constructed using a layer-by-layer composite method.

[0014] The preferred preparation steps of the multilayer metal composite film of the present invention are as follows:

[0015] The substrate surface is subjected to N layers of metal nanoparticle film (metal layer) composite layer by layer to form a multilayer composite precursor in which N layers of metal nanoparticle film are sequentially composited; wherein, before the second to the Nth composite, the surface of the previous metal nanoparticle film is pre-dried naturally and subjected to plasma treatment.

[0016] This invention has found that the layer-by-layer composite approach of the multilayer metal composite film, combined with plasma assistance, helps to overcome the problem of mismatch between metal nanoparticle layers (metal layers), and is more conducive to subsequent halide ion-assisted cyclic voltammetric electrochemical nanowelding, and more conducive to the preparation of porous metals.

[0017] The metal nanoparticle film composite process described in this invention is as follows: a first layer of metal nanoparticle film (metal particle layer) is first formed on a substrate, and then after drying-plasma treatment, a second layer of metal nanoparticle film is composited. Then, after natural drying-plasma treatment, the next layer of metal particle layer is composited. The natural drying-plasma-metal nanoparticle film composite process is repeated N-1 times to obtain a porous precursor with N layers of metal nanoparticle film composited layer by layer.

[0018] In this invention, the substrate is a non-conductive substrate, preferably a non-conductive polyethylene terephthalate (PET) substrate.

[0019] In this invention, the material, particle size, particle shape, and number of layers of the metal particles can be adjusted according to the application requirements of the porous metal material.

[0020] Preferably, the metal particles are at least one of gold, silver, palladium, platinum, iron, copper, and aluminum.

[0021] In this invention, the metal particles are nanospheres with a particle size of 3–100 nm; preferably 3–70 nm; more preferably 10–50 nm; and even more preferably 15–20 nm.

[0022] Preferably, N (the number of metal layers in the three-dimensional precursor) is an integer greater than or equal to 2, preferably an integer from 2 to 350; more preferably an integer from 2 to 20, even more preferably 5 to 15 layers, and most preferably 12 to 15 layers.

[0023] In this invention, the surface of the metal nanoparticle thin film layer (metal layer) is dried to evaporate the solvent and solidify the film itself. Then, the metal nanoparticle thin film layer is subjected to plasma treatment, and then a single-layer metal nanoparticle thin film is laminated onto it.

[0024] In this invention, the power during the plasma treatment process is less than or equal to 80W; preferably 20-50W, and more preferably 30-40W. Research has found that N2 plasma treatment with optimized power is beneficial for improving the property compatibility of interlayer metal nanoparticles and for the composite formation of metal nanoparticle thin film layers.

[0025] In this invention, the plasma treatment gas atmosphere is at least one of N2 and an inert gas.

[0026] In this invention, the N2 plasma treatment time is 0.1-5 min, preferably 0.5-1 min.

[0027] The metal particles of this invention, taking Au as an example, are prepared as follows: a hydrothermal method is used to synthesize a metal nanoparticle sol, followed by self-assembly of the metal nanoparticles at the water-oil interface, and then transfer at the water-gas interface to form a multilayered metal nanoparticle film. The hydrothermal synthesis of the metal nanoparticle sol is, for example, achieved using the Frens citrate reduction method, with citrate ions as a reducing agent and surfactant to prepare metal nanoparticle sols of different particle sizes. The size of the metal nanoparticles is adjusted by the amount of citrate added. The water-oil interface self-assembly is, for example, achieved by placing the prepared metal nanoparticle sol in a beaker, then adding cyclohexane to form a clear water-oil interface, followed by adding ethanol as an inducing agent to initiate the transfer of metal nanoparticles from the lower aqueous phase to the water-oil interface, and then self-assembling them into a dense Au nanoparticle film. After removing the upper oil phase, the metal nanoparticle film at the water-gas interface is transferred to the solid substrate by immersion in the liquid and then smoothly lifted upwards. In this invention, the metal nanoparticle films in each layer refer to dense film layers mainly composed of a single layer of metal nanoparticles, but the possibility of multiple layers of stacked metal nanoparticles in some areas cannot be ruled out. Preferably, the gap between metal particles in the same layer is less than or equal to 2 nm; preferably, the gap between metal particles between layers is less than or equal to 1 nm; and preferably, they are in contact with each other.

[0028] In this invention, after the final layer of metal nanoparticle film is composited, it is dried and then subjected to subsequent halide ion-assisted electrochemical nanowelding.

[0029] In this invention, the electrochemical nanowelding is performed based on a three-electrode electrochemical cyclic voltammetry scan: the operation is as follows:

[0030] The three-dimensional precursor to be welded is used as the working electrode, and it is assembled with the counter electrode and the reference electrode to form a three-electrode system. Then, cyclic voltammetry electrochemical nano-welding is carried out in the electrolyte containing halide ions.

[0031] Preferably, the counter electrode is a Pt counter electrode or a carbon counter electrode;

[0032] Preferably, the reference electrode is at least one of a saturated mercurous sulfate electrode, a reversible hydrogen electrode, a saturated calomel electrode, an Ag / AgCl electrode, and a Hg / HgO electrode; more preferably, it is a saturated mercurous sulfate electrode.

[0033] In this invention, a halogen ion-assisted cyclic voltammetric electrochemical nanowelding process is employed, which can significantly improve the nanowelding effect and increase the nanowelding efficiency. Based on this innovation, further control of the halogen ion type, the number of cycles of cyclic voltammetry, and the scan rate helps to further achieve synergy. While ensuring excellent efficiency, it also significantly improves the nanowelding effect, reduces local or overall over-welding and structural collapse problems, and improves the weld ligament and pore structure.

[0034] Preferably, the halide ion is F. - Cl - ,Br - and I - At least one of them, preferably F - and / or Cl - ;

[0035] Preferably, the concentration of halide ions in the electrolyte is 2 μM to 2.0 M; more preferably 2 mM to 1.0 M; even more preferably 2 to 200 mM; and most preferably 2 to 25 mM.

[0036] Preferably, the halide ions are added in the form of sodium salts, potassium salts, ammonium salts, or acids of halide ions;

[0037] Preferably, the electrolyte in the electrolyte solution is a water-soluble acid, alkali, or salt; preferably an acid, and more preferably at least one of sulfuric acid and perchloric acid;

[0038] Preferably, the concentration of the electrolyte in the electrolyte solution is 0.01–2.0 M, more preferably 0.1–1 M, and even more preferably 0.4–0.6 M.

[0039] Preferably, the number of electrochemical cyclic voltammetry cycles for the welding treatment is less than or equal to 50, more preferably 1 to 10, and even more preferably 2 to 5 cycles;

[0040] Preferably, the scan rate of the electrochemical cyclic voltammetry for the welding treatment is 1–1000 mV / s, more preferably 5–500 mV / s, even more preferably 5–500 mV / s, and even more preferably 40–60 mV / s.

[0041] Preferred embodiment of the present invention:

[0042] The metal particles have a diameter of 3–70 nm, the three-dimensional precursor has 2–20 layers, the reference electrode is a saturated mercurous sulfate electrode, the concentration of halide ions in the electrolyte is 2 mM–1.0 M, the concentration of electrolyte in the electrolyte is 0.01–2.0 M, the number of electrochemical cyclic voltammetry cycles is 1–10, and the scan rate is 5–500 mV / s.

[0043] Further optimizations include a metal particle size of 15–50 nm, a three-dimensional precursor layer number of 5–15, a saturated mercurous sulfate electrode as the reference electrode, a halide ion concentration of 2 mM–200 mM in the electrolyte, an electrolyte concentration of 0.1–1 M in the electrolyte, an electrochemical cyclic voltammetry cycle number of 1–10, and a scan rate of 5–500 mV / s.

[0044] More preferably, the halide ion is F. - or Cl - The metal particles have a diameter of 15–20 nm, the three-dimensional precursor has 5–15 layers, the reference electrode is a saturated mercurous sulfate electrode, the concentration of halide ions in the electrolyte is 2 mM–20 mM, the concentration of electrolyte in the electrolyte is 0.4–0.6 M, the number of electrochemical cyclic voltammetry cycles is 2–5, and the scan rate is 40–60 mV / s.

[0045] The present invention has found that, under the combined control of the aforementioned process and parameters, synergy can be further achieved, which helps to further solve the problems of over-soldering and etching, and further improve the effect and efficiency of nano-welding.

[0046] This invention discloses a preferred method for preparing halide ion-assisted high-efficiency electrochemical nanowelding of three-dimensional nanoporous metals, comprising the following steps:

[0047] Step (1):

[0048] Metal nanoparticle (metal particle) sols of different particle sizes were prepared by hydrothermal method.

[0049] Step (2):

[0050] Metal nanoparticles are assembled into a dense metal nanoparticle film via self-assembly at the water-oil interface, followed by oil layer transfer. Subsequently, the dense metal nanoparticle film is transferred to a solid substrate from the water-air interface.

[0051] Step (3):

[0052] A multilayer composite precursor is formed by performing N layer-by-layer composite treatments of metal nanoparticle films on the substrate surface, resulting in N layers of metal nanoparticle films being sequentially composited. Before the second to Nth composite treatments, the surface of the previous metal nanoparticle film is subjected to natural drying and plasma treatment. N is an integer greater than or equal to 2.

[0053] Step (4):

[0054] Three-dimensional nanoporous gold was prepared by subjecting a multilayer composite precursor to a halide-ion-assisted electrochemical nanowelding process in an electrolyte solution containing halide ions.

[0055] The preferred method for preparing three-dimensional nanoporous gold using halide ion-assisted electrochemical nanowelding combines water-oil interface self-assembly, water-gas interface transfer, natural drying-plasma treatment, and other processes to prepare multilayer metal nanoparticle films. By electrochemically treating the multilayer metal nanoparticle films in an electrolyte solution containing halide ions, the Ostwald ripening process between metal nanoparticles is enhanced, thereby achieving electrochemical nanowelding between metal nanoparticles and obtaining three-dimensional nanoporous gold.

[0056] This invention innovatively discovers that by performing electrochemical treatment in an electrolyte solution containing halide ions, the dissolution and diffusion process of atoms on the surface of metal nanoparticles is accelerated, which can enhance the Ostwald ripening process of metal nanoparticles. Electrochemical nanowelding between metal nanoparticles can be achieved under efficient, low-temperature, and controllable conditions, thereby efficiently preparing high-purity three-dimensional nanoporous metals. A preferred embodiment of this invention provides a feasible bottom-up electrochemical nanowelding strategy for preparing high-purity three-dimensional nanoporous metals from metal nanoparticles of different sizes. First, multilayer metal nanoparticle films (denoted as x-ML y-nm metal nanoparticle films, where x and y represent the number of layers (i.e., the number of monolayers) and the size (diameter) of the metal nanoparticles, respectively, are obtained through interfacial self-assembly and layer-by-layer transfer techniques. Then, these films are electrochemically treated in an electrolyte solution containing halide ions to perform electrochemical nanowelding. Therefore, this bottom-up approach is highly tunable, allowing for fine-tuning of the three-dimensional nanoporous metal nanostructure by altering the type and concentration of halide ions, the scan rate and number of cycles in the electrochemical treatment process, the thickness of the multilayer metal nanoparticle film, and the size of the initial metal nanoparticles. Theoretically, it can be extended to fabricating various nanoporous materials by using other nanoparticles with different properties, sizes, shapes, and compositions as initial states.

[0057] The present invention also provides a three-dimensional nanoporous metal, such as nanoporous gold (NPG), prepared by the above method.

[0058] In this invention, thanks to the special synthesis method, the product can be endowed with special material and morphological characteristics. Moreover, the product obtained by the method has excellent performance.

[0059] The present invention also provides applications of the three-dimensional nanoporous metal prepared by the above preparation method, using it in at least one device in optics, electricity, electrochemistry, and sensing.

[0060] Beneficial effects:

[0061] 1. This invention proposes a novel approach to constructing three-dimensional nanoporous metals using halide ion-assisted cyclic voltammetry electrochemical nanowelding; and the combination of halide ions and electrochemical cyclic voltammetry can achieve synergy, significantly improving welding efficiency and effectiveness.

[0062] 2. Further, by combining the control of the type and concentration of halide ions in the halide-containing electrolyte system, the scan rate and number of cycles of cyclic voltammetry during electrochemical treatment, and the thickness and initial size of the multilayer metal nanoparticle film, synergistic effects can be achieved. This can successfully solve problems such as the difficulty in composite porous metal films and the difficulty in uniform fusion within and between layers. Electrochemical nanowelding of three-dimensional porous materials can be realized, and the performance of the prepared materials can be improved. For example, the three-dimensional NPG prepared by the method of this invention has good conductivity, high electrochemical active sites, and numerous surface plasmon resonance active sites, thus showing great application prospects in nanodevices, electrocatalysis, nanosensing, and surface Raman enhancement.

[0063] 3. This invention can achieve the regulation of multilayer pore structure by jointly controlling parameters such as the type and concentration of halide ions, the scan rate and number of cycles of cyclic voltammetry during electrochemical treatment, the thickness of the multilayer metal nanoparticle film and the size of the initial metal nanoparticles. The technical solution has strong controllability.

[0064] 4. The halide ion-assisted electrochemical nanowelding method used in this invention is based on the Ostwald curing process of metal nanoparticles. This not only avoids the problems of high energy consumption, resource waste, use of corrosive media, and residual sacrificial components (affecting the purity of the obtained nanoporous gold) in dealloying and template methods, but also overcomes the problems of wasted gold dissolution source, inability to easily transfer the obtained nanoporous gold to different substrates, and the limitation of the size of the obtainable nanoporous gold by the size of the original gold electrode in electrochemical anodizing. Moreover, it can achieve efficient nanowelding between metal nanoparticles without the need for solder.

[0065] 5. The method of the present invention is simple, efficient, low-cost, environmentally friendly, highly adjustable, and widely applicable. It is applicable to the welding of almost all conductive nanomaterials and the preparation of porous materials. Attached Figure Description

[0066] To more clearly illustrate the technical solutions in the examples of the present invention or the prior art, the accompanying drawings used in the description of the examples or the prior art will be briefly introduced below.

[0067] Figure 1 : 15-ML 16-nm Au nanoparticle films in the absence and presence of 20mM Cl -Cyclic voltammetry curves of NPG were obtained after treatment with ions in 0.5 M H2SO4 solution by electrochemical cyclic voltammetry (scan rate of 50 mV / s) for different numbers of cycles.

[0068] in, Figure 1 In the figures, (a) is in 0.5M H2SO4 solution (circulation number 1-10 times); (b) is in 0.5M H2SO4 + 20mM KCl solution (circulation number 1-10 times).

[0069] Figure 2 : 15-ML 16-nm Au nanoparticle films in the absence and presence of 20mM Cl - SEM characterization of NPG obtained after electrochemical cyclic voltammetry (scan rate 50 mV / s) treatment with different numbers of cycles in 0.5 M H2SO4 solution containing ions.

[0070] in, Figure 2 In the diagram, (ac) represents electrochemical cyclic voltammetry treatments in 0.5M H₂SO₄ solution for (a) 1 cycle, (b) 5 cycles, and (c) 10 cycles; (df) represents electrochemical cyclic voltammetry treatments in 0.5M H₂SO₄ + 20mM KCl solution for (d) 1 cycle, (e) 5 cycles, and (f) 10 cycles.

[0071] Figure 3 : Schematic diagram of the process and mechanism for preparing three-dimensional NPG by a halide ion-assisted high-efficiency electrochemical method.

[0072] Figure 4 : 15-ML 16-nm Au nanoparticle films in Cl containing different concentrations - SEM characterization of NPG obtained after electrochemical cyclic voltammetry (scan rate 50 mV / s) treatment with different numbers of cycles in 0.5 M H2SO4 solution containing ions.

[0073] in, Figure 4 In the diagram, (ab) represents treatment in 0.5M H2SO4 + 20mM KCl solution for (a) 1 cycle and (b) 2 cycles; (cd) represents treatment in 0.5M H2SO4 + 200mM KCl solution for (c) 1 cycle and (d) 2 cycles.

[0074] Figure 5 : Cyclic voltammetry curves of 15-ML 16-nm Au nanoparticle films in 0.5M H2SO4 + 20mM KCl solution at different scan rates.

[0075] in, Figure 5 In the above, (a) is 500 mV / s; (b) is 50 mV / s; and (c) is 5 mV / s.

[0076] Figure 6 SEM images of 15-ML 16-nm Au nanoparticle films in 0.5M H2SO4 + 20mM KCl solution after electrochemical cyclic voltammetry treatment at different scan rates.

[0077] in, Figure 6 In the diagram, (a) is 500 mV / s; (b) is 50 mV / s; and (c) is 5 mV / s.

[0078] Figure 7 : Cyclic voltammetry curves of 15-ML 16-nm Au nanoparticle films in 0.5M H2SO4 solutions containing different types of halide ions.

[0079] in, Figure 7 In the above, (a) is a 0.5M H2SO4 + 20mM KI solution; (b) is a 0.5M H2SO4 + 20mM KBr solution; (c) is a 0.5M H2SO4 + 20mM KCl solution; and (d) is a 0.5M H2SO4 + 20mM KF solution.

[0080] Figure 8 SEM images of NPG obtained by electrochemical cyclic voltammetry treatment with 15-ML 16-nm Au nanoparticle films in 0.5M H2SO4 solutions containing different types of halide ions for different numbers of cycles.

[0081] in, Figure 8 In the above, (ab) were scanned for 5 cycles in 0.5M H2SO4 + 20mM KI solution and 10 cycles in (a) and (b) respectively; (cd) were scanned for 5 cycles in 0.5M H2SO4 + 20mM KBr solution and 10 cycles in (c) and (d) respectively; (ef) were scanned for 5 cycles in 0.5M H2SO4 + 20mM KCl solution and 10 cycles in (e) and (f) respectively; (gh) were scanned for 5 cycles in 0.5M H2SO4 + 20mM KF solution and 10 cycles in (g) and (h) respectively.

[0082] Figure 9 SEM images of NPG obtained by electrochemical cyclic voltammetry treatment of 8-ML 30-nm Au nanoparticle films in 0.5M H2SO4 solutions containing different types of halide ions for different numbers of cycles.

[0083] in, Figure 9In the table, (ab) represents scanning (a) for 5 cycles and (b) for 10 cycles in 0.5M H2SO4 + 20mM KI solution; (cd) represents scanning (c) for 5 cycles and (d) for 10 cycles in 0.5M H2SO4 + 20mM KBr solution; (ef) represents scanning (e) for 5 cycles and (f) for 10 cycles in 0.5M H2SO4 + 20mM KCl solution; and (gh) represents scanning (g) for 5 cycles and (h) for 10 cycles in 0.5M H2SO4 + 20mM KF solution.

[0084] Figure 10 SEM images of NPG obtained by electrochemical cyclic voltammetry treatment of 5-ML 50-nm Au nanoparticle films in 0.5M H2SO4 solutions containing different types of halide ions for different numbers of cycles.

[0085] in, Figure 10 In the diagram, (ab) represents scanning (a) for 5 cycles and (b) for 10 cycles in 0.5M H₂SO₄ + 20mM KI solution; (cd) represents scanning (c) for 5 cycles and (d) for 10 cycles in 0.5M H₂SO₄ + 20mM KBr solution; (ef) represents scanning (e) for 5 cycles and (f) for 10 cycles in 0.5M H₂SO₄ + 20mM KCl solution; and (gh) represents scanning (g) for 5 cycles and (h) for 10 cycles in 0.5M H₂SO₄ + 20mM KF solution.

[0086] Figure 11 : 15-ML 16-nm Au nanoparticle films in different concentrations of F - SEM characterization images of NPG obtained after treatment with 0.5M H2SO4 solution of ions followed by electrochemical cyclic voltammetry with different numbers of cycles.

[0087] in, Figure 11 In the diagram, (ac) represents scanning (a) 1 lap, (b) 3 laps, and (c) 5 laps in 0.5M H2SO4 + 20mM KF solution; (df) represents scanning (d) 1 lap, (e) 3 laps, and (f) 5 laps in 0.5M H2SO4 + 2mM KF solution.

[0088] Figure 12 SEM image of 15-ML 16-nm NPG obtained by electrochemical cyclic voltammetry treatment (scan rate 50 mV / s) in 0.5 M H2SO4 + 2 mM KF solution for 3 cycles (for pore size distribution statistics).

[0089] Figure 13Statistical analysis of the pore size distribution of 15-ML 16-nm NPG obtained by electrochemical cyclic voltammetry treatment (50 mV / s) in 0.5 M H₂SO₄ + 2 mM KF solution.

[0090] Figure 14 Electrocatalytic performance of 15-ML 16-nm Au nanoparticle films in 0.5M H2SO4 + 2mM KF solution for the electro-oxidation of ethanol was characterized before and after 3 cycles of electrochemical cyclic voltammetry treatment in 0.5M KOH + 1.0M CH3CH2OH solution.

[0091] in, Figure 14 In the figure, (a) is the cyclic voltammetry curve (scan rate 10 mV / s); (b) is the AC impedance spectrum and corresponding fitted equivalent circuit under open circuit voltage; (c) is the it curve under polarization voltage of 1.1 V.

[0092] Figure 15 The graph shows the relationship between the oxidation peak current density and the number of cycles for a 15-ML 16-nm NPG electrode prepared by electrochemical cyclic voltammetry treatment in 0.5M H2SO4 + 2mM KF solution for 3 cycles at a scan rate of 50mV / s. This is the cyclic voltammetry curve (scan rate 10mV / s) of the electrode in 0.5M KOH + 1.0M CH3CH2OH solution after preparing a 15-ML 16-nm Au nanoparticle film. Detailed Implementation Plan

[0093] The embodiments of the present invention will be described in detail below with reference to examples. However, those skilled in the art will understand that the following examples are for illustrative purposes only and should not be considered as limiting the scope of the invention. Unless otherwise specified in the examples, conventional conditions or conditions recommended by the manufacturer are followed. Reagents or instruments whose manufacturers are not specified are all commercially available conventional products.

[0094] The method provided by this invention involves assembling 16nm, 30nm, and 50nm Au nanoparticles obtained by the classic Frens method (i.e., reducing chloroauric acid in an environment where trisodium citrate is used as a stabilizer and reducing agent) into a dense Au nanoparticle film through interfacial self-assembly. Subsequently, the film is subjected to efficient, low-temperature, and controllable halide ion-assisted electrochemical nanowelding to achieve the preparation of three-dimensional nanoporous gold.

[0095] The specific steps of the method of this invention are as follows:

[0096] (a) The concentration of Au nanoparticle sol obtained by the Frens citrate reduction method (a hydrothermal method) is approximately 57.91 μg nanoparticles / mL; the metal nanoparticles are spherical particles.

[0097] The steps for synthesizing Au nanoparticle sol are as follows: First, 100 mL of 0.294 mM HAuCl4 solution was added to a 250 mL three-necked flask, which was then placed in a constant-temperature heated magnetic stirrer containing a 135 °C oil bath (the oil bath temperature was corrected using a mercury thermometer to avoid temperature errors affecting the experimental results). Once the oil bath temperature stabilized at 135 °C and the HAuCl4 solution in the three-necked flask was boiling vigorously, 3.6 mL, 1.5 mL, and 0.88 mL of 1% sodium citrate solution were rapidly added under vigorous magnetic stirring to prepare Au nanoparticle sols with diameters of 16 nm, 30 nm, and 50 nm, respectively. The reaction was continued for 45 min, after which heating and stirring were stopped. The three-necked flask was removed from the oil bath and cooled to room temperature for later use. Water was used as the solvent to disperse the Au nanoparticles, and citrate ions added before the synthesis reaction were used as the stabilizer.

[0098] (b) Au nanoparticles were assembled into a dense Au nanoparticle film by water-oil interface self-assembly and transferred to a 4 mm × 10 mm PET substrate. After natural drying, the film was subjected to nitrogen plasma treatment and then transferred repeatedly to obtain a precursor composed of multilayer Au nanoparticle films.

[0099] The interface self-assembly steps are as follows: First, 20 mL of the prepared Au nanoparticle sol (prepared in step a) is placed in a 50 mL beaker; then, about 5 mL of cyclohexane is added to form a clear water-oil interface; then, 10 mL of ethanol is rapidly injected to induce the Au nanoparticles to self-assemble into a dense Au nanoparticle film at the water-oil interface; finally, the cyclohexane layer on the Au nanoparticle film at the water-oil interface is removed, and the Au nanoparticle film is transferred to the corresponding substrate. After the Au nanoparticle film is naturally dried in air, it is subjected to surface plasma treatment (N2 atmosphere) at 40 W for 30 s to support the transfer of the next layer of Au nanoparticle film. Depending on the preparation requirements, the interface self-assembly-drying-plasma treatment is repeated N-1 times. After the last assembly, it is naturally dried in air to obtain a multilayer precursor-free material with N monolayer Au nanoparticle films layer by layer.

[0100] The multilayer Au nanoparticle film formed as described above is the object to be welded in this invention.

[0101] (c) The multilayer Au nanoparticle film prepared as above was placed in an electrolyte solution containing halide ions and electrochemically nanowelded on it. The electrochemical properties and microstructure of the three-dimensional nanoporous gold obtained after electrochemical nanowelding under different conditions were characterized.

[0102] In the halide ion-assisted electrochemical nanowelding process, the electrolyte solution used is a 0.5M H2SO4 acidic solution;

[0103] In the halide ion-assisted electrochemical nanowelding process, the type of halide ion used is F. - Cl - ,Br - and I - ;

[0104] Preferably, in the halide ion-assisted electrochemical nanowelding process, the halide ions are fixed as Cl... - The cyclic voltammetry scan rate was 50 mV / s to investigate Cl. - The effects of the concentration and the number of cycles of cyclic voltammetry at different concentrations on the obtained three-dimensional nanoporous gold structures were investigated to optimize the operating conditions.

[0105] Preferably, in the halide ion-assisted electrochemical nanowelding process, the halide ions are fixed as Cl... - The concentration of halide ions was 20 mM. The effects of halide ion scan rate and the number of cycles of cyclic voltammetry at different scan rates on the obtained three-dimensional nanoporous gold structure were investigated, and the operating conditions were optimized.

[0106] As a preferred method, in the halide ion-assisted electrochemical nanowelding process, the concentration of halide ions was fixed at 20 mM and the cyclic voltammetry scan rate was 50 mV / s. The effects of the type of halide ions and the number of cycles of cyclic voltammetry under different halide ion types on the obtained three-dimensional nanoporous gold structure were investigated, and the operating conditions were optimized.

[0107] As a preferred method, in the halide ion-assisted electrochemical nanowelding process, the concentration of halide ions was fixed at 20 mM and the cyclic voltammetry scan rate was 50 mV / s. The influence of the particle size of Au nanoparticles under different halide ion types on the obtained three-dimensional nanoporous gold structure was investigated, and the operating conditions were optimized.

[0108] Preferably, in the halide ion-assisted electrochemical nanowelding process, the halide ions are fixed as F. - The scan rate for cyclic voltammetry is 50 mV / s, based on F - The effects of the concentration and the number of cycles of cyclic voltammetry at different concentrations on the obtained three-dimensional nanoporous gold structures were investigated to optimize the operating conditions.

[0109] Example 1

[0110] The following method was used to synthesize Au nanoparticles via the Frens citrate reduction method (a hydrothermal method):

[0111] Step 1: Prepare 100 mL of 0.294 mM HAuCl4 solution and add it to a 250 mL three-necked flask. Then place it in a constant temperature magnetic stirrer with a 135 °C oil bath (use a mercury thermometer to correct the temperature of the oil bath to avoid temperature errors affecting the experimental results).

[0112] Step 2: When the oil bath temperature stabilizes at 135℃ and the HAuCl4 solution in the three-necked flask boils vigorously, 3.6 mL, 1.5 mL, and 0.88 mL of 1% sodium citrate solution are quickly added under vigorous magnetic stirring to prepare Au nanoparticle sols with diameters of 16 nm, 30 nm, and 50 nm, respectively. After continuing the reaction for 45 min, heating and stirring are stopped, and the three-necked flask is removed from the oil bath and cooled to room temperature for later use.

[0113] Example 2

[0114] The interfacial self-assembly and transfer of Au nanoparticles were performed using the following method:

[0115] Step 1: Place the prepared 20 mL Au nanoparticle sol (prepared based on the method of Example 1) into a 50 mL beaker, and then add about 5 mL of cyclohexane to form a clear water-oil interface.

[0116] Step 2: Rapidly inject 10 mL of ethanol to induce Au nanoparticles to self-assemble into a dense metal nanoparticle film at the water-oil interface. Then, remove the cyclohexane layer on the Au nanoparticle film at the water-oil interface and transfer the dense Au nanoparticle film to a 4 mm × 10 mm PET substrate. After natural drying, a single-layer Au nanoparticle film is obtained.

[0117] Furthermore, layer-by-layer self-assembly transfer processing is performed according to the preparation requirements. Before transferring the next layer, the Au nanoparticle film is pre-dried naturally and then treated with N2 plasma (40W) for 30 seconds. After the last layer is transferred, it is naturally dried to obtain an N-layer composite multilayer Au nanoparticle film. This invention mainly focuses on 15-ML 16-nm Au nanoparticle films, 8-ML 30-nm Au nanoparticle films, and 5-ML 50-nm Au nanoparticle films.

[0118] Example 3

[0119] Halogen ion-assisted electrochemical nanowelding of multilayer Au nanoparticle films (constructed by the method in Example 2) was performed according to the following method:

[0120] Step 1: Using an electrochemical workstation as a power source, electrochemical nano-welding is performed in a standard three-electrode system, wherein the multilayer Au nanoparticle film prepared above is used as the working electrode, a platinum sheet is used as the counter electrode, and a saturated mercurous sulfate electrode is used as the reference electrode.

[0121] Step 2: The 15-ML 16-nm Au nanoparticle film, dried and transferred onto a PET substrate, was placed in 20mM Cl-free and 20mM Cl-free environments, respectively. - Electrochemical cyclic voltammetry was performed for 10 cycles in a 0.5 M H₂SO₄ solution containing KCl ions at a scan rate of 50 mV / s. The cyclic voltammetry curves during the treatment were recorded, and the three-dimensional NPG obtained after electrochemical treatment was characterized by SEM microstructure.

[0122] In step 2, by Figure 1 15-ML 16-nm Au nanoparticle films in the absence and presence of 20mM Cl - A comparison of the cyclic voltammetric curves of ions in a 0.5 MH₂SO₄ solution shows that Cl… - The presence of ions results in an additional Au oxidation peak at approximately 0.58 V (vs MSE). Figure 1 (b)), and the potential of this oxidation peak is much larger than the initial oxidation peak potential of Au in a 0.5 M H₂SO₄ solution without halogen ions, which is approximately 0.71 V. Figure 1 (a) is low. Correspondingly, an additional reduction peak potential of approximately 0.45 V appears at about 0.29 V, lower than that of Au oxides in 0.5 M H₂SO₄ solution without halide ions. Clearly, the introduction of Cl... - After ionization, a lower oxidation potential was observed, indicating that Au surface atoms are more easily oxidized, and the dissolution process is more likely to occur, meaning that the material supply for nano-welding between Au nanoparticles is more abundant. Simultaneously, the lower reduction potential promotes the dissolution of AuCl4. - Complexed ions achieve a more stable and uniform welding effect between Au nanoparticles through more complete diffusion. This can also be achieved through... Figure 2 The SEM images of 15-ML 16-nm Au nanoparticle films after undergoing the same electrochemical cyclic voltammetry treatment in two solutions show that, after 10 cycles of electrochemical cyclic voltammetry treatment in a halogen-free 0.5M H₂SO₄ solution, only a weak welding effect exists between the Au nanoparticles. Figure 2 (ac)), but after only one cycle of electrochemical voltammetry treatment in 0.5M H2SO4 + 20mM KCl solution, a good welding effect between Au nanoparticles was achieved. Figure 2 (d)). This indicates that the halide ion Cl... -The presence of [a specific substance] significantly promotes the nano-welding between Au nanoparticles, enabling the rapid electrochemical preparation of NPG. However, it is worth mentioning that in the presence of Cl [a specific substance]... - Electrochemical cyclic voltammetry treatment in 0.5M H₂SO₄ solution does not necessarily lead to better welding results with more cycles. For example... Figure 2 As shown in (df), the welding effect between Au nanoparticles continuously strengthens from cycle 1 to cycle 5, and the nanoligaments also continuously widen. However, when the electrochemical cyclic voltammetry treatment reaches cycle 10, the nanoligaments that were originally welded to the wider NPG are etched away, replaced by narrower nanoligaments and larger nanopores. Therefore, in the process of preparing NPG by electrochemical cyclic voltammetry treatment of multilayer Au nanoparticle films in a halide-containing H2SO4 solution, the number of cycles of electrochemical cyclic voltammetry treatment needs to be optimized in conjunction with the concentration of halide ions. Based on the above... Figure 1 and Figure 2 In the presence and absence of Cl, 15-ML 16-nm Au nanoparticle films were subjected to... - The difference in NPG obtained after electrochemical welding treatment in 0.5 M H₂SO₄ solution shows that introducing a low concentration of halide ions into the 0.5 M H₂SO₄ solution can promote the dissolution, diffusion, and redeposition of Au during electrochemical cyclic voltammetry treatment. This provides a richer material supply for nano-welding between Au nanoparticles, thereby achieving rapid nano-welding between Au nanoparticles and enabling more efficient NPG preparation. Therefore, the process and mechanism of halide ion-assisted high-efficiency electrochemical preparation of three-dimensional NPG can be found in [reference needed]. Figure 3 .

[0123] Example 4

[0124] Compared to Example 3, the only difference is the change in the concentration of halide ions in the electrolyte; the difference lies in the process:

[0125] A 15-ML 16-nm Au nanoparticle film, dried and transferred onto a PET substrate, was placed in 0.5M H₂SO₄ + 20mM KCl solution and 0.5M H₂SO₄ + 200mM KCl solution, respectively, and subjected to two cycles of electrochemical cyclic voltammetry at a scan rate of 50 mV / s. The microstructure of the three-dimensional NPG obtained after electrochemical treatment was characterized by SEM.

[0126] Depend on Figure 4 (a,b) shows that in a solution of 0.5M H₂SO₄ + 20mM KCl, the welding effect of the 15-ML 16-nm Au nanoparticle film after two cycles of electrochemical cyclic voltammetry treatment is better than that after one cycle. The resulting NPG has wider nano-ligaments, smaller nanopores, and fewer nanopores. Conversely, Figure 4 In (c,d), in a solution of 0.5 M H₂SO₄ + 200 mM KCl, the NPG nanoligaments prepared by 2 cycles of electrochemical cyclic voltammetry on 15-mL 16-nm Au nanoparticle films were wider than those prepared by 1 cycle of cyclic voltammetry, but had larger nanopore sizes. Furthermore, after the same number of cycles, at lower Cl₂ concentrations... - NPG nanoribbons prepared in a 0.5 M H₂SO₄ + 20 mM KCl solution were wider and had smaller nanopores, exhibiting better nano-welding performance. This indicates that in a Cl-containing solution... - In a high-concentration 0.5M H₂SO₄ + 200mM KCl solution, excessive oxidation and etching of Au occurs. This overabundance of material supply is detrimental to the nano-welding between Au nanoparticles and the preparation of NPG. Therefore, in the process of preparing NPG through electrochemical cyclic voltammetry treatment of multilayer Au nanoparticle films in a halide-containing H₂SO₄ solution, the concentration of halide ions is a crucial factor that needs to be carefully controlled.

[0127] Example 5

[0128] Compared with Example 3, the only difference is the adjustment of the cyclic voltammetric scan rate, as follows:

[0129] A 15-mL 16-nm Au nanoparticle film, dried and transferred onto a PET substrate, was placed in a 0.5M H₂SO₄ + 20mL M KCl solution and subjected to 5 cycles of electrochemical cyclic voltammetry at scan rates of 500mV / s, 50mV / s, and 5mV / s, respectively. Cyclic voltammetry curves were recorded during the treatment, and the three-dimensional NPG obtained after electrochemical treatment was characterized by SEM microstructure.

[0130] Different scan rates in electrochemical cyclic voltammetry treatment imply different rates of potential change and durations at each potential. To investigate the effect of scan rate on welding performance, 15-mL 16-nm Au nanoparticle films were subjected to electrochemical cyclic voltammetry treatment in 0.5M H₂SO₄ + 20mM KCl solution at different scan rates. Figure 5 It can be seen that compared with a scan rate of 50 mV / s ( Figure 5 (b)) at a scan rate of 500 mV / s ( Figure 5 (a)), AuCl4 - The proportion of complex ions is greatly reduced, which leads to the diffusion capacity of AuCl4. -Complex ions are no longer the primary material supplier for the nano-welding between Au nanoparticles. Instead, Au oxides with poor diffusion capabilities passivate the electrode surface. This leads to excessive welding between adjacent Au nanoparticles within the fabricated NPG, further causing partial structural collapse within the three-dimensional porous structure due to excessively wide nanoligaments. In other words, the excessively wide nanoligaments replace some of the nanopores. Figure 6 (a)), while the nanoporous structure is greatly reduced, which is not conducive to the practical application of the prepared NPG. However, when the scan rate is 5 mV / s, AuCl4... - The proportion of complex ions increased significantly, even exceeding that of Au oxides that passivate the electrode surface. Figure 5 (c) This leads to AuCl4, which can diffuse freely in the electrolyte solution. - The amount of complexed ions far exceeds the material supply required for nano-welding Au nanoparticles (which can also be understood as the oxidation and dissolution rate of Au being far greater than the reduction and redeposition rate of Au compounds), thus resulting in excessive oxidation etching of Au. Figure 6 (c) is unfavorable for NPG preparation. In contrast, at a scan rate of 50 mV / s, 15-ML 16-nm Au nanoparticle films were subjected to electrochemical cyclic voltammetry treatment in 0.5 M H2SO4 + 20 mM KCl solution (c) Figure 5 (b) The NPG nanostructure obtained after preparation ( Figure 6 (b) is better. Therefore, in the process of preparing NPG by electrochemical cyclic voltammetry treatment of multilayer Au nanoparticle films in H2SO4 solution containing halide ions, the structure of the prepared NPG can be controlled by the electrochemical cyclic voltammetry scan rate.

[0131] Example 6

[0132] Compared to Example 3, the only difference is the adjustment of the halide ion type and the three-dimensional precursor, specifically:

[0133] 15-ML 16-nm Au nanoparticle films, 8-ML 30-nm Au nanoparticle films, and 5-ML 50-nm Au nanoparticle films, dried and transferred onto a PET substrate, were subjected to cyclic voltammetry treatment at a scan rate of 50 mV / s for 10 cycles in 0.5 M H₂SO₄ + 20 mM KI solution, 0.5 M H₂SO₄ + 20 mM KBr solution, 0.5 M H₂SO₄ + 20 mM KCl solution, and 0.5 M H₂SO₄ + 20 mM KF solution, respectively. The microstructure of the three-dimensional NPG obtained after electrochemical treatment was characterized by SEM.

[0134] To further optimize the nanostructure of the prepared NPG, this invention also investigated the welding effect of multilayer Au nanoparticle films in 0.5M H₂SO₄ solutions containing different types of halide ions. Electrochemical cyclic voltammetry treatment was performed on 15-mL 16-nm Au nanoparticle films in 0.5M H₂SO₄ + 20 mM KI solution, 0.5M H₂SO₄ + 20 mM KBr solution, 0.5M H₂SO₄ + 20 mM KCl solution, and 0.5M H₂SO₄ + 20 mM KF solution, respectively. Figure 7 From the cyclic voltammetry curve in (ac), it can be seen that in I - ,Br - and Cl - In the presence of ions, the oxidation peak potentials of Au and halide complexes are approximately 0.7 V, 0.38 V, and 0.58 V, respectively, while the corresponding reduction peak potentials are approximately 0 V, 0.1 V, and 0.29 V, respectively. Meanwhile, the oxidation peak potentials of Au and F... - The oxidation peak formed by the complexed ions is covered by the oxidation peak (approximately 0.71 V) that passivates the Au surface, and the reduction peak is also covered by the corresponding reduction peak (approximately 0.45 V). Figure 7 (d) Therefore, the oxidation peak potentials for the formation of Au-halogen ion complexes are ordered as follows: The reduction peak potentials are ordered as follows: AuI4 - The oxidation potential of the complexed ions is close to the oxide formation potential that can passivate the Au electrode surface, resulting in insufficient material supply for nano-welding between Au nanoparticles in 0.5M H2SO4 + 20mM KI solution. In addition, I - The larger atomic mass and volume lead to AuI4 - The complexed ions have a larger mass and volume, resulting in a slower diffusion rate in the electrolyte. In addition, AuI4... - The complex ions have the lowest reduction peak potential, making it difficult for them to undergo reduction-redeposition. This further hinders the supply of material for nano-welding between Au nanoparticles, thus limiting the potential for 15-ML 16-nm Au nanoparticles ( Figure 8 (a,b)), 8-ML 30-nm Au nanoparticles ( Figure 9 (a,b)) and 5-ML 50-nm Au nanoparticles ( Figure 10 (a,b) The welding performance of the films in 0.5 M H₂SO₄ + 20 mM KI solution was not as good as that in the other three solutions under the same conditions. Conversely, in 0.5 M H₂SO₄ + 20 mM KBr solution, AuBr₄… -The oxidation peak potential formed by complex ions is the lowest, while its corresponding reduction peak potential is relatively low. This indicates that the oxidation and dissolution process of Au is relatively easy to occur, while the reduction and redeposition process is not easy to carry out. This inevitably leads to an oversupply of material for nano-welding between Au nanoparticles, which in turn causes excessive oxidation and etching of Au. Figure 8 (c,d), Figure 9 (c,d) and Figure 10 (c,d)) is unfavorable for NPG preparation. However, comparing the cyclic voltammetry curves and SEM characterization images of the prepared NPG under different conditions reveals that, regardless of particle size, the welding effect of multilayer Au nanoparticle films in 0.5M H₂SO₄ + 20mM KCl solution is the best under the same treatment conditions. This is due to the perfect match between the oxidation dissolution rate of Au, the diffusion rate of the compound in the electrolyte, and the rate of compound reduction and redeposition. Figure 8 (e,f), Figure 9 (e,f) and Figure 10 (e,f)). However, in reality, the excessively large size of the nano-ligaments caused by excessive nano-welding is not conducive to the practical application of NPG. Therefore, in comparison, the NPG prepared by electrochemical cyclic voltammetry treatment of multilayer Au nanoparticle films in 0.5M H2SO4 + 20mM KF solution has the best performance. Figure 8 (g,h), Figure 9 (g,h), Figure 10 (g,h)) This avoids both etching caused by excessive oxidation and structural collapse caused by excessive welding, and most importantly, ensures good welding results. Furthermore, using 15-ML and 16-nm Au nanoparticles with different Au NPs sizes ( Figure 8 (g,h)), 8-ML 30-nm Au nanoparticles ( Figure 9 (g,h)) and 5-ML 50-nm Au nanoparticles ( Figure 10 The morphological characterization of NPG obtained by electrochemical cyclic voltammetry treatment of (g,h) films in 0.5 M H2SO4 + 20mM KF solution showed that the 15-ML 16-nm Au nanoparticle films had better welding performance and finer nano-ligament structure, which is more conducive to their application in the field of electrocatalysis.

[0135] Example 7

[0136] Compared to Example 3, the only difference is that the conditions for cyclic voltammetric electrochemical nanowelding are adjusted, specifically:

[0137] 15-ML 16-nm Au nanoparticle films transferred to a PET substrate and dried were then subjected to different concentrations of F. -Electrochemical cyclic voltammetry was performed for 5 cycles in a 0.5 M H₂SO₄ solution containing ions at a scan rate of 50 mV / s. The three-dimensional NPG obtained after electrochemical treatment was characterized by SEM microstructure.

[0138] To further optimize the nanostructure of the prepared NPG, this invention also investigated the presence of F in 0.5 M H2SO4 solution. - The effect of ion concentration on the structure of the prepared NPG. 15-mL 16-nm Au nanoparticle films were subjected to electrochemical cyclic voltammetry treatment with different numbers of cycles in 0.5M H₂SO₄ + 20mM KF and 0.5M H₂SO₄ + 2mM KF solutions, respectively. The microstructure of the NPG obtained after treatment was then characterized by SEM. Figure 11 The results showed that the NPG obtained after three cycles of electrochemical cyclic voltammetry on 15-ML 16-nm Au nanoparticle films in 0.5M H₂SO₄ + 2mM KF solution had the best structure (i.e., ensuring sufficient bonding without over-bonding, and the size of the main nano-ligaments was close to the diameter of the initial Au NPs). Furthermore, based on the method reported in the literature, the nanopore size distribution of the NPG obtained after three cycles of electrochemical cyclic voltammetry on 15-ML 16-nm Au nanoparticle films in 0.5M H₂SO₄ + 2mM KF solution was statistically analyzed. The size of 1200 nanopores in the SEM characterization image of the obtained NPG was measured. Figure 12 Statistical results show that most nanopore sizes are in the range of 2-20 nm. Figure 13 The average pore size is 9.2 nm.

[0139] Example 8 - Performance Study

[0140] The electrocatalytic performance of 15-ML 16-nm Au nanoparticle films and 15-ML 16-nm NPG prepared by electrochemical cyclic voltammetry treatment (scan rate 50 mV / s) in 0.5 M H2SO4 + 2 mM KF solution for the electro-oxidation of ethanol was investigated. Figure 14 (a) Cyclic voltammetry curves of 15-mL 16-nm Au nanoparticle films and 15-mL 16-nm NPG in 0.5M KOH + 1.0M CH3CH2OH solution. During the positive scan, the positive oxidation peak at approximately 1.25V corresponds to the oxidation of ethanol; during this period, OH... - Anions are first adsorbed onto the surface of the Au nanoparticle thin-film electrode, leading to the oxidation of ethanol within it. The positive oxidation current density of ethanol on the 15-ML 16-nm NPG electrode is 2.6076 mA / cm². 2) is a 15-ML 16-nm Au nanoparticle thin film electrode (1.7450mA / cm) 2 The peak current density was 1.4943 times that of the reported peak current density, and it showed a significant advantage over the reported peak current density in the literature. This indicates that the electrocatalytic performance of 15-ML 16-nm NPG, which was prepared by electrochemically cycling 3 times in 0.5M H2SO4 + 2mM KF solution, was significantly enhanced for the electrocatalytic oxidation of ethanol. Figure 14 (b) The AC impedance spectra of 15-ML 16-nm Au nanoparticle films and 15-ML 16-nm NPG in 0.5M KOH + 1.0M CH3CH2OH solution at open-circuit voltage and their equivalent circuit (inset). Both electrodes show semi-circular shapes in the high-frequency region, and no obvious Warburg impedance line was observed in the low-frequency region, indicating that the reaction kinetics are controlled by the charge transfer process. Based on the fitting results of the equivalent circuit, the Ri of 15-ML 16-nm Au nanoparticle films and 15-ML 16-nm NPG is shown. s The values ​​are 46.87 and 32.65 Ω·cm, respectively. 2 R ct 7460 and 6144 Ωcm respectively 2 Clearly, 15-ML 16-nm NPG exhibits lower impedance, indicating that the synergistic effect of higher conductivity, more exposed active sites, and a larger electrochemical surface area leads to faster and more efficient electrochemical reactions when 15-ML 16-nm NPG is used as the working electrode. Subsequently, the stability of 15-ML 16-nm Au nanoparticle films and 15-ML 16-nm NPG in 0.5M KOH + 1.0 M CH3CH2OH solution was investigated using chronoamperometry. Figure 14 (c)). After polarization treatment at 1.1V (vs. RHE) for 4000s, the oxidation peak current densities of 15-ML 16-nm Au nanoparticle films and 15-ML 16-nm NPG films increased from 1.1639 and 1.5633 mA / cm², respectively. 2 Decreased to 0.0371 and 0.3854 mA / cm 2 Before and after prolonged 1.1V constant potential polarization treatment, the initial current density and termination current density of 15-ML 16-nm NPG were 1.34 and 10.39 times that of 15-ML 16-nm Au nanoparticle film, respectively. This indicates that the prepared 15-ML 16-nm NPG has better stability than 15-ML 16-nm Au nanoparticle film.

[0141] Finally, the oxidation peak current density of the cyclic voltammetry curve (scan rate 10 mV / s) of the 15-mL 16-nm NPG electrode in 0.5M KOH + 1.0M CH3CH2OH solution was analyzed as a function of the number of cycles. Figure 15 The study investigated the cyclic voltammetry of 15-mL 16-nm NPG in 0.5M KOH + 1.0M CH3CH2OH solution, based on the variation of peak current with cycle number. This process can be divided into two stages. In the first stage (cycles 1-21), the ratio of oxidation peak current density to initial peak current increases with cycle number. This is because more surface active sites are exposed in this stage, promoting the electro-oxidation of ethanol. The oxidation peak current density increases by 47.40% compared to the initial current density. In the second stage (cycles 22-400), the ratio of oxidation peak current density to initial current density decreases with increasing cycle number, dropping to 65.15% of the initial current density after 400 cycles. This can be attributed to the reduction of surface active sites in the Au nanoparticle film after repeated electrochemical cycling.

Claims

1. A method for preparing three-dimensional nanoporous metals by halide ion-assisted electrochemical nanowelding, characterized in that, Three-dimensional nanoporous metals were prepared by cyclic voltammetric electrochemical nanowelding of the three-dimensional precursors to be welded in an electrolyte containing halide ions. The three-dimensional precursor is composed of stacked metal particles with nano gaps between them to be welded; the metal particles are gold particles; the metal particles are nanospheres with a particle size of 3 to 100 nm. The three-dimensional precursor is a multilayer metal composite film formed by stacking two or more single-layer metal layers sequentially; the number of layers in the multilayer metal composite film is an integer greater than or equal to 2; the gap between metal particles in the same layer is less than or equal to 2 nm; the gap between metal particles between layers is less than or equal to 1 nm. The halide ion is F - Cl - ,Br - and I - At least one of the following; in the electrolyte, the concentration of the halide ions is 2 μM ~ 2.0 M; During the electrochemical nanowelding process, the number of electrochemical cyclic voltammetry cycles is 1 to 10; the scan rate of the electrochemical cyclic voltammetry is 5 to 500 mV / s.

2. The method as described in claim 1, characterized in that, The preparation steps of the multilayer metal composite film are as follows: A multilayer composite precursor is formed by sequentially compositing N layers of metal nanoparticle films on the substrate surface. Before the second to Nth compositing, the surface of the previous metal nanoparticle film is pre-dried and subjected to plasma treatment.

3. The method as described in claim 2, characterized in that, The power during the plasma treatment process is 20-50 W; The plasma treatment gas atmosphere is at least one of N2 and an inert gas; The plasma treatment time is 0.5 to 1 minute.

4. The method as described in claim 1, characterized in that, The metal particles are nanospheres with a particle size of 3~70 nm; The number of layers in the multilayer metal composite film is an integer from 2 to 350; The metal particles between the layers are in contact with each other.

5. The method as described in claim 4, characterized in that, The number of layers in the multilayer metal composite film is an integer from 2 to 20.

6. The method as described in claim 1, characterized in that, The electrochemical nanowelding was performed based on a three-electrode electrochemical cyclic voltammetry scan: the operation was as follows: The three-dimensional precursor to be welded is used as the working electrode, and it is assembled with the counter electrode and the reference electrode to form a three-electrode system. Then, cyclic voltammetric electrochemical nano-welding is performed in the electrolyte containing halide ions. The counter electrode is a Pt counter electrode or a carbon counter electrode; The reference electrode is at least one of the following: saturated mercurous sulfate electrode, reversible hydrogen electrode, saturated calomel electrode, Ag / AgCl electrode, and Hg / HgO electrode.

7. The method as described in claim 1, characterized in that, In the electrolyte, the concentration of the halide ions is 2 mM to 1.0 M.

8. The method as described in claim 1, characterized in that, The halide ions are added in the form of sodium salts, potassium salts, ammonium salts, or acids.

9. The method as described in claim 1, characterized in that, The electrolyte in the electrolyte solution is a water-soluble acid, alkali or salt.

10. The method as described in claim 9, characterized in that, The electrolyte in the electrolyte is at least one of sulfuric acid and perchloric acid.

11. The method as described in claim 10, characterized in that, The concentration of the electrolyte in the electrolyte solution is 0.01 ~ 2.0 M.

12. The method according to any one of claims 1 to 11, characterized in that, The metal particles have a diameter of 3 to 70 nm, the three-dimensional precursor has 2 to 20 layers, the reference electrode is a saturated mercurous sulfate electrode, the concentration of halide ions in the electrolyte is 2 mM to 1.0 M, the concentration of electrolyte in the electrolyte is 0.01 to 2.0 M, the number of electrochemical cyclic voltammetry cycles is 1 to 10, and the scan rate is 5 to 500 mV / s.

13. The method as described in claim 12, characterized in that, The metal particles have a diameter of 15–50 nm, the three-dimensional precursor has 5–15 layers, the reference electrode is a saturated mercurous sulfate electrode, the concentration of halide ions in the electrolyte is 2 mM–200 mM, the concentration of electrolyte in the electrolyte is 0.1–1 M, the number of electrochemical cyclic voltammetry cycles is 1–10, and the scan rate is 5–500 mV / s.

14. The method as described in claim 13, characterized in that, The halide ion is F - or Cl - The metal particles have a diameter of 15-20 nm, the three-dimensional precursor has 5-15 layers, the reference electrode is a saturated mercurous sulfate electrode, the concentration of halide ions in the electrolyte is 2 mM-20 mM, the concentration of electrolyte in the electrolyte is 0.4-0.6 M, the number of electrochemical cyclic voltammetry cycles is 2-5, and the scan rate is 40-60 mV / s.

15. A three-dimensional nanoporous metal prepared by the method of any one of claims 1 to 14.

16. An application of the three-dimensional nanoporous metal of any one of claims 1 to 14, wherein it is used in at least one device in optics, electronics, electrochemistry, or sensing.

Citation Information

Patent Citations

  • Nanoporous gold / potassium vanadate and nanoporous gold / potassium manganate aqueous potassium ion microbattery and preparation method and application thereof

    CN109103457A

  • Ostwald nanometer welding method

    CN113634743A

  • Three-dimensional nano porous metal and direct current welding preparation method and application thereof

    CN114619163A